ANALISIS YURIDIS TENTANG PASAL 1057 KUHPERDATA SEBAGAI DASAR DALAM MENGAJUKAN PERMOHONAN PENOLAKAN HAK ATAS WARIS DI PENGADILAN NEGERI - Avriantara, Fally (LPPM Universitas Bina Bangsa, 2024)
Article 1057 of the Civil Code mandates that the provisions for denial of inheritance rights must be stated expressly at the Registrar's Office of the District Court in whose jurisdiction the inheritance is open. However, there is no clearer or firmer explanation regarding what is meant by the phrase